Cytological effects of Dimethoate and Lambda-Cyhalothrin on Pollen Grain Cells Reproduction and Development - Bawa, Y. M.; Kalimullah, S.; Wagini, N. H.; Abdullahi, M.; Bello, I.; Garga, M. A.; Qabasiyu, M. M.; Ma’aruf, M.; Salihu, A. A. (UMYU Journal of Microbiology Research, 2025)
Study’s Excerpt: